Análise de interações verbais em um blog jornalístico: possíveis relações de controle entre jornalista e leitores e leitores entre si - Wang, Maria Auxiliadora de Lima (2008)
In his analysis of verbal behavior, Skinner emphasizes the importance of considering the behavior of the listener to obtain a proper understanding of the behavior of the speaker and vice versa. In this work, verbal interactions in a journalistic blog were analyzed to look for possible relations of control among the participants of the blog: from the journalist to the readers and vice versa, and among the readers themselves. Thirty-seven texts were analyzed; they were published by the journalist to his blog during three and a half days, in the period immediately after the TAM airplane accident that took place in Sao Paulo on July, 17, 2007, as well as 1673 comments on these texts. Comments were classified according to their target - whether they were addressed to the journalist or to other readers, or had no specific target. These comments were also classified into categories such as agreement, disagreement and contribution. The results suggest: 1) the existence of mutual control between the journalist and his readers and among the readers themselves; 2) strong control of the topics relating to the accident on the writing of the participants of the blog; 3) differential control by the journalist on the readers writing behavior compared to the control among readers themselves; 4) strong influence of emotional variables on the writing behavior of the participants of the blog. In this respect, however, it was concluded that, although the data allow supposing the existence of these control relations, further studies are needed to clarify these supposed control relationships. The average delay between the publication of a text and the publication of its first comment was 2 hours and 37 minutes. This delay was less than an hour in 22 out of 37 texts analyzed. These data suggest that new technologies, such as Internet and its byproducts, such as blogs, can reduce extraordinarily the interval between the verbal behavior and its effects, while at the same time the reach of the product of that behavior can be dramatically increased. Thus, these new technologies should be considered in the planning of contingencies for the teaching and the study of the verbal behavior. In addition, the blogs, by allowing the inclusion of new individuals in the process of news production, may increase the possibilities of countercontrol by the reader over the press and cause the relationship between reader and press to become less distant